Chemical modification and micropatterning of Si(100) with oligonucleotides - Yin, H; Brown, T; Greef, R; Wilkinson, J; Melvin, T (2004)
A method for the reliable attachment of oligonucleotides to silicon (1 0 0) surfaces in patterns is described. UV light exposure of silicon (1 0 0) coated with alkenes functionalized with carboxylic acid groups and derivatives results in covalent attachment to the silicon surface. The carboxyl-terminated (and derivatives) surfaces act as a substrate for the chemistry of the subsequent attachment of oligonucleotides. Illustrated are our results gained for optimisation of the surface attachment chemistry and the characterisation of the surface with scanning electron microscopy, epifluorescence microscopy and ellipsometry. © 2004 Elsevier B.V. All rights reserved.